PERAN GURU DALAM MENANAMKAN PERILAKU SOPAN SANTUN DI TK ISLAM PAS ASSAKIINAH MANTINGAN NGAWI - Yudhiarti, Ndaru Putri; Eka Milasari , Devita; Putra Azharin, Barrin (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2023)
The discussion in this research is about the role of teachers in instilling polite behavior in the Pas Assakiinah Mantingan Ngawi Islamic Kindergarten. The background of this research is that there are six students who still ignore the teacher's orders, there are children who run around in class, children tend to be less able to control their emotions when interacting with friends, besides that there are students who have a tendency to have communication barriers so that ignoring the teacher's orders does not It can be implemented immediately, for example when a guest says hello to a child with special needs (ABK) who doesn't want to answer straight away. This research aims to find out the role of teachers in instilling polite behavior at the Pas Assakiinah Mantingan Ngawi Islamic Kindergarten and what are the obstacles in instilling polite behavior at the Pas Assakiinah Mantingan Ngawi Islamic Kindergarten. The research method used by researchers is descriptive qualitative research. Data sources obtained from observation data, documentation and interviews. The researcher's data analysis method uses descriptive analysis. The results of the research show that there are four roles of the teacher in instilling polite behavior in the Pas Assakiinah Mantingan Ngawi Islamic Kindergarten, namely 1) The role of the teacher as an educator, 2) The role of the teacher as a motivator, 3) The role of the teacher as a caregiver, 4) The role of the teacher as an example. There are two obstacles faced by Pas Assakiinah Islamic Kindergarten teachers, namely: 1) parental factors, namely parental educational background, lack of understanding of religious knowledge, differences in parenting styles received by parents when they were small, parents being busy so that child care is fully provided. to foster parents, what is taught at school may not necessarily be practiced at home. 2) student factors, there are students with special needs (ABK) who have a tendency to have communication barriers so that when carrying out the teacher's orders they are not carried out directly, there are children who still ignore the teacher's orders, there are children who run around in the classroom, with emotions the children tend to be less able. control emotions when interacting with friends.